Penampilan dan Kualitas Telur Puyuh yang Diberi Pakan Mengandung Produk Fermentasi dengan Neurospora crassa - Nuraini Nuraini; Sabrina Sabrina; S.A. Latif (Universitas Andalas, 2011)
An experiment was conducted to determine the effect of feeding products fermented by Neurospora crassa on quail performances and egg quality. 200 quail layers were randomly allocated into 20 pens. This experiment was arranged in a completely randomized design (CRD) with four dietary treatments: 0%, 3%, 6%, 9% and 12% product fermented by Neurospora crassa in the diets and four replications. Variable measured were feed comsumption, egg production, feed conversion, egg cholesterol and egg yolk colour. Data were analized by CRD and Duncan Multiple Range Test (DMRT). Results of the experiment indicated that feed comsumption, egg production, feed conversion were not affected (P>0.05) but egg cholesterol and egg yolk colour were affected (P<0.01) by using product fermented in the diets for quails. Results of Duncant Multiple Range Test indicated that egg cholesterol in E treatment (used 12% products fermented) was the lowest than other treatment, but the highest on egg yolk colour . The conclusion of the experiment that up to 12% products fermented by Neurospora crassa can be used in the diet of quail and can increase the quality of quail egg (egg low cholesterol).